Gold nanoparticle-adjuvanted S protein induces a strong antigen-specific IgG response against severe acute respiratory syndrome-related coronavirus infection, but fails to induce protective antibodies and limit eosinophilic infiltration in lungs - Sekimukai, Hanako; Iwata-Yoshikawa, Naoko; Fukushi, Shuetsu; Tani, Hideki; Kataoka, Michiyo; Suzuki, Tadaki; Hasegawa, Hideki; Niikura, Kenichi; Arai, Katsuhiko; Nagata, Noriyo (Microbiology and immunology, 2020)
The spike (S) protein of coronavirus, which binds to cellular receptors and mediates membrane fusion for cell entry, is a candidate vaccine target for blocking coronavirus infection. However, some animal studies have suggested that inadequate immunization against severe acute respiratory syndrome coronavirus (SARS-CoV) induces a lung eosinophilic immunopathology upon infection. The present study evaluated two kinds of vaccine adjuvants for use with recombinant S protein: gold nanoparticles (AuNPs), which are expected to function as both an antigen carrier and an adjuvant in immunization; and Toll-like receptor (TLR) agonists, which have previously been shown to be an effective adjuvant in an ultraviolet-inactivated SARS-CoV vaccine. All the mice immunized with more than 0.5 µg S protein without adjuvant escaped from SARS after infection with mouse-adapted SARS-CoV; however, eosinophilic infiltrations were observed in the lungs of almost all the immunized mice. The AuNP-adjuvanted protein induced a strong IgG response but failed to improve vaccine efficacy or to reduce eosinophilic infiltration because of highly allergic inflammatory responses. Whereas similar virus titers were observed in the control animals and the animals immunized with S protein with or without AuNPs, Type 1 interferon and pro-inflammatory responses were moderate in the mice treated with S protein with and without AuNPs. On the other hand, the TLR agonist-adjuvanted vaccine induced highly protective antibodies without eosinophilic infiltrations, as well as Th1/17 cytokine responses. The findings of this study will support the development of vaccines against severe pneumonia-associated coronaviruses.